Utility of "reposition-flap" in the reconstruction of the avulsed thumb. Issue 38 (24th September 2021) - Pertea, Mihaela; Ciobanu, Petru; Velenciuc, Natalia; Poroch, Vladimir; Filip, Alexandru; Moraru, Dan Cristian; Lunca, Sorinel; Veliceasa, Bogdan
Abstract : Abstract: Injuries that result in thumb amputation cause a loss of 50% of hand function. Microsurgical replantation remains the gold standard of thumb reconstruction techniques. The non-microsurgical technical variants of thumb reconstruction described so far aim to create a neo-thumb of adequate length, stable, opposable, sensitive, and last but not least esthetically pleasing appearance. Avulsion of the distal phalanx and the absence of the nail will determine a functional deficit but also an unesthetic appearance. When replantation is not possible or the patient refuses to "sacrifice" another anatomical region for thumb reconstruction, the "reposition-flap" technique can be used. Although often controversial, this surgical technique deserves proper attention and should be used in some cases. We studied a group of 32 patients with distal thumb amputations. In patients with amputations in zone II according to Tamai, with interphalangeal joint preservation, the thumb was reconstructed using "reposition-flap" with an O'Brien flap in 15 cases. In the remaining 17 cases where the amputation was at the level of the interphalangeal joint, we used the same technique, but the thumb neopulp was reconstructed with the Littler heterodigital neurovascular flap harvested from the ulnar border of the middle finger in 11 cases or radial border of the ring finger in 6 cases. The results were evaluated from a functional (Kapandji score), sensitive (2-point discrimination, Semmes-Weinstein test) but also esthetically (patient satisfaction) point of view. Donor site morbidity, cold intolerance, the presence of nail dystrophy, and bone resorbtion were also assessed. The disabilities of the arm, shoulder and hand score was evaluated for each patient. Although various surgical and microsurgical techniques for thumb reconstruction are described, when choosing the technique to use we must first consider patient's wishes. A well-informed patient will be able to make, with the surgeon, the best decision for him concerning the reconstruction option.